Experimental study on the uniform distribution of gas-liquid two-phase flow in a variable-aperture deflector in a parallel flow heat exchanger. (April 2020) - Wu, Xuehong; Gao, Zhicheng; Meng, Hao; Wang, Yanling; Cheng, Chuanxiao
Highlights: Discusses of distribution uniformity of the gas and liquid two-phase fluid. Compares distribution characteristics in different deflectors headers. Experimentally distribution uniformity in microchannel heat exchanger headers. Abstract: The uneven distribution of refrigerants in tube of a microchannel heat exchanger has a serious impact on the performance of the microchannel heat exchanger. The addition of a deflector in the microchannel heat exchanger can play a role in the secondary distribution. The difference in structure significantly affects the distribution uniformity of the refrigerant. In this paper, air and water are used as two-phase working fluids, and the effect of inserting a deflector on the distribution uniformity of the fluid in the header of a parallel flow heat exchanger with horizontal round tubes and 24 parallel flat tubes is studied. The superficial velocity ranges of the gas and liquid were 2.47–3.04 m/s and 0.67–0.86 m/s, respectively. Six kinds of deflector structures were studied in the experiment, in which the total cross-sectional area of the deflector and the total flow area of the flat tubes were tested as both different and the same. The experimental results show that under the experimental conditions, the uniformity of the gas and liquid distributions in the three-symmetrical deflector structure is better, followed by the two-symmetrical deflector structure, and then the uniform aperture deflector structure is the worst. Through a comparative analysis of these six deflector structures, the distribution uniformity of the gas and liquid two-phase fluid in the A1 variable-aperture deflector is the best. The open-area of the deflector is 670.39 mm 2, which is the best value and is different from the total flow area of the flat tubes.